Kinerja Public Area Attendant dalam Menangani Kebersihan Public Area di Hotel Grand Mercure Solo Baru (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This final project aims to determine: (1) Job desk of public area attendant in cleaning public areas at the Grand Mercure Solo Baru Hotel (2) Performance of public area attendant in handling public area cleanliness. This study uses a qualitative research method by obtaining data through interviews, observations, documentation and literature studies. The data analysis technique used in this study consists of four steps, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the research that has been conducted, it was concluded that the performance of the public area attendant is quite good in handling public area cleanliness because it is done every day with a daily checklist carried out on each shift, and with the job desk, the duties and responsibilities of the public area attendant in maintaining and preserving the cleanliness of hotel assets are clearly written. However, there are obstacles, namely, equipment and cleaning materials are not always available because staff do not conduct an inventory every month. Therefore, it is necessary to procure goods to improve the performance of the public area attendant in handling public area cleanliness at the Grand Mercure Solo Baru Hotel.